2013
DOI: 10.3389/fneur.2013.00144
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Mimicking an Arteriovenous Malformation

Abstract: Abnormal cerebral vasculature can be a manifestation of a vascular malformation or a neoplastic process. We report the case of a patient with angiography-negative subarachnoid hemorrhage (SAH) who re-presented 3 years later with a large intraparenchymal hemorrhage. Although imaging following the intraparenchymal hemorrhage was suggestive of arteriovenous malformation, the patient was ultimately found to have an extensive glioblastoma associated with abnormal tumor vasculature. The case emphasizes the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Intra-cavernous aneurysms (IAs) (aSAH-N) may coexist with PAs, meningiomas, glioma, retinoblastoma, acoustic neurilemmoma, RCC, and cerebral malformations (Raskind, 1965 ; Gonzales-Portillo and Valdivia, 2006 ; Vogel et al, 2011 ; Akutsu et al, 2014 ). Although na-ne-SAH is the rarest type of SAH, it occurs due to bleeding from vascularization of the pituitary apoplexy (PA), cerebral metastases (CM), malignant glioma (MG), acoustic neuroma (AN), schwannoma of the cranial nerve, cervical meningiomas, cervical spinal cord hemangioblastoma, and spinal meningeal carcinomatosis with negative angiography (Gliemroth et al, 1999 ; Garg et al, 2004 ; Javalkar et al, 2009 ; Khanna et al, 2013 ; Heit et al, 2017 ). Drug-related SAH is relevant to cocaine abuse, and no aneurysms are shown or present during angiography (Rinkel et al, 1991a ).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-cavernous aneurysms (IAs) (aSAH-N) may coexist with PAs, meningiomas, glioma, retinoblastoma, acoustic neurilemmoma, RCC, and cerebral malformations (Raskind, 1965 ; Gonzales-Portillo and Valdivia, 2006 ; Vogel et al, 2011 ; Akutsu et al, 2014 ). Although na-ne-SAH is the rarest type of SAH, it occurs due to bleeding from vascularization of the pituitary apoplexy (PA), cerebral metastases (CM), malignant glioma (MG), acoustic neuroma (AN), schwannoma of the cranial nerve, cervical meningiomas, cervical spinal cord hemangioblastoma, and spinal meningeal carcinomatosis with negative angiography (Gliemroth et al, 1999 ; Garg et al, 2004 ; Javalkar et al, 2009 ; Khanna et al, 2013 ; Heit et al, 2017 ). Drug-related SAH is relevant to cocaine abuse, and no aneurysms are shown or present during angiography (Rinkel et al, 1991a ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many reports [10][11][12][13][14][15][16][17] have indicated that there may be a relationship between CCM and intracranial tumors such as glioma, meningioma, and schwannoma. There also have been some reports of glioblastoma presenting as suspected arteriovenous malformation [1,10] . There may be two types of this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma is the most common intracranial tumor and the most frequent cause of hemorrhage in brain tumors. ICH caused by glioblastoma is usually located in the cerebral hemispheres, basal ganglia, and corpus callosum [1] . A few hypotheses have been proposed to explain the etiology of tumor-associated hemorrhage.…”
Section: Discussionmentioning
confidence: 99%